Bernard Bolzano 24 Erbauungsreden. 1808-1820 - Strasser, Kurt F. (2001)
Bernard Bolzano (1781-1848) during his time as a professor of religious studies (1805-1820) had to give a speech to the whole community of students every sunday during the academic year. This was a very influential position which also caused his dismissal in 1820. Here we have the textual edition of the lectures or sermons he gave during his period of office. The critical edition involves the missing sermons found in Prague archives. The complete edition of Bolzano's sermons will be published in the Bolzano-Gesamtausgabe Frommann Holzboog, 2A15-25.